Bridging the knowledge gap on the distribution and typology of vermetid bioconstructions along the Maltese coastline: an updated assessment - FRANZITTA, GIULIO; MARRONE, ALEESIO; GAUCI, ADAM; GALDIES, JOHANN; MANGANO, MARIA CRISTINA; SARA, GIANLUCA; DEIDUN, ALAN (Mediterranean Marine Science, 2022)
In the Maltese Islands, insufficient attention has been paid to vermetid reefs, endemic Mediterranean bioconstructions widely distributed along the southern part of the basin. As a result, this is a largely-overlooked coastal ecosystem despite the multitude of ecosystem services it provides. The perennial urban development in the Maltese Islands calls for the adoption of urgent action to protect coastal habitats, in particular bioconstructions that increase biodiversity and contribute to mitigating the effects of climate change. The objective of our study was to extensively document the presence and typology of the vermetid reef ecosystems along the coast of Malta and Gozo, assessing the occurrence of putative anthropogenic threats on the same ecosystem. Quantitative measurements were additionally taken to morphologically characterize the recorded bioconstructions. Furthermore, we tested the human pressure effect on the density of vermetid individuals and associated biodiversity. “True” trottoirs were only documented along the south-east coast of Malta, where unfortunately land reclamation projects are expected to be implemented. Although no direct relation between a number of assessed human activities and the density of vermetid individuals was reported in the current study, we suggest the conduction of further studies to investigate the influence of specific disturbances on the conservation status of this ecosystem. This study expands the existing knowledge on the status of vermetid reefs in the Maltese Islands and calls for management and conservation actions to preserve this bioconstruction.